A critical review of MANET testbed using mobile robot technology - Muchtar, Farkhana; Abdullah, Abdul Hanan; Md Arshad, Marina; Abd Wahab, Mohd Helmy; Ahmmad, Siti Nor Zawani; Abdul-Salaam, Gaddafi (IOP Publishing, 2018)
This paper is a continuation of our previous paper under the same topic, MANET testbed using mobile robot technology. In our previous paper, we studied the topic by scrutinizing all the technical aspects and presented it as a technical review. However in this paper, we study the topic and presents it as a critical review that dwells into four aspect, namely (i) purpose, a ccessibility and s cope of testbed facilities, (ii) usability and c ontrollability of robot mobility in t estbed facilities, (iii) repeatability and r e producibility of real m obility in t estbeds, and (iv) tools for MANET implementation, deployment and d ebugging for experiments. With the wealth of information on the topic provided in this paper, the content of this paper is expected to be a source of reference for MANET researchers who are at a crossroad when selecting the preferred mobi le robot technology and approach to sui t thei r own speci f ic needs.